The modulation of electrothermal distribution by square spiral kirigami structure in graphite paper. (29th December 2022) - Jingye, Gao; Yinglin, Qin; Bojun, Yang; Chang, Wang; Anzuo, Qin; Si, Xiao; Jun, He
Abstract: A square spiral incision was introduced into a 15 × 15 cm regular quadrilateral conductive film to study the modulation of electrothermal distribution by kirigami structure. Based on the simulation of finite element method, the transition from thermal focusing to thermal defocusing could be achieved by increasing the length of connection between adjacent modules. The effective electrothermal area can be increased by nearly two times through increasing the length increment of the notch length between adjacent modules. The maximum temperature was decreased from 254 °C to 44 °C, and the temperature difference was adjusted from 76 °C to 4 °C by increasing the number of kirigami module. Through the contact temperature measurement experiment on graphite paper kirigami structure, the trends could be verified. By creating an equivalent circuit model and considering the influence of heat conduction, the peak temperature at the center of the structure and the decrease of the overall temperature could be explained. By deriving the relationship between the temperature of conductive film of kirigami structure with time and position, the electrothermal characteristics of previously reported graphene kirigami structure could be predicted.